Literasi Sadar Pajak terhadap Tax Compliance (Studi Empiris pada Mahasiswa Fakultas Pendidikan Ekonomi dan Bisnis di Universitas Pendidikan Indonesia) - Nabila Ghina Athaya; Stephent Ferdynannd Valentino (Epistemik: Indonesian Journal of Social and Political Science, 2021)
This study aims to analyze the effect of tax awareness literacy on tax compliance. The type of this research is the students of the Indonesian Education University, Faculty of Economics and Business Education. The data used in this research is using primary data with the distribution through a questionnaire. Data analysis techniques in this study used descriptive analysis and multiple regression. The results of this study indicate that tax literacy has an effect on tax compliance for students of the Indonesian Education University, Faculty of Economics and Business Education.